2007
DOI: 10.1086/508774
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Invasive Aspergillosis with Posaconazole in Patients Who Are Refractory to or Intolerant of Conventional Therapy: An Externally Controlled Trial

Abstract: Although the study predates extensive use of echinocandins and voriconazole, these findings demonstrate that posaconazole is an alternative to salvage therapy for patients with invasive aspergillosis who are refractory to or intolerant of previous antifungal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
551
4
32

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 719 publications
(609 citation statements)
references
References 24 publications
22
551
4
32
Order By: Relevance
“…The response rate to standard-or high-dose L-AmB, haematologica | 2010; 95(4) © F e r r a t a S t o r t i F o u n d a t i o n caspofungin or voriconazole was already reported to range from 32% to 53%. [24][25][26][27][28][29][30] The percentage of success reported in those studies is lower than that observed in our registry, which ranged from 64% to 82%. This could be explained by the very restrictive criteria for response evaluation in pivotal trials.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Ncontrasting
confidence: 61%
“…The response rate to standard-or high-dose L-AmB, haematologica | 2010; 95(4) © F e r r a t a S t o r t i F o u n d a t i o n caspofungin or voriconazole was already reported to range from 32% to 53%. [24][25][26][27][28][29][30] The percentage of success reported in those studies is lower than that observed in our registry, which ranged from 64% to 82%. This could be explained by the very restrictive criteria for response evaluation in pivotal trials.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Ncontrasting
confidence: 61%
“…TDM is used to avoid treatment failure, resistance, or toxicity. The optimal plasma trough levels (with HPLC/MS) are 1-4 mg/L for itraconazole, 2-6 mg/L for voriconazole, and greater than 1 mg/L for posaconazole suspension [60][61][62]. The newer tablet or intravenous formulation of posacoanzole is more likely to achieve target plasma levels but there is limited evidence for routine TDM.…”
Section: Invasive Aspergillosismentioning
confidence: 99%
“…Posaconazole, another triazole with activity against moulds, is available in oral formulation only and demonstrates moderate variability in absorption. In a salvage study for IA in patients previously treated with amphotericin products, favorable response was observed in 42% [96] and among SOT recipients specifically, 58% had successful outcomes on treatment. As with voriconazole, drug interactions can be frequently seen with posaconazole, absorption is variable, and therapeutic drug level monitoring is encouraged.…”
Section: Aspergillusmentioning
confidence: 98%